Acute dacryocystitis: another clinical manifestation of sporotrichosis - Dayvison Francis Saraiva Freitas; Iluska Augusta Rocha Lima; Carolina Lemos Curi; Livia Jordão; Rosely Maria Zancopé-Oliveira; Antonio Carlos Francesconi do Valle; Maria Clara Gutierrez Galhardo; Andre Luiz Land Curi (Memorias do Instituto Oswaldo Cruz, 2014)
Sporotrichosis associated with exposure to domestic cats is hyperendemic in Rio de Janeiro, Brazil. A review of the clinical records at our institute revealed four patients with clinical signs of dacryocystitis and a positive conjunctival culture for Sporothrix who were diagnosed with Sporothrix dacryocystitis. Three patients were children (< 13 years of age) and one patient was an adult. Two patients reported contact with a cat that had sporotrichosis. Dacryocystitis was associated with nodular, ulcerated lesions on the face of one patient and with granulomatous conjunctivitis in two patients; however, this condition manifested as an isolated disease in another patient. All of the patients were cured of the fungal infections, but three patients had chronic dacryocystitis and one patient developed a cutaneous fistula. Sporotrichosis is usually a benign disease, but may cause severe complications when the eye and the adnexa are affected. Physicians, especially ophthalmologists in endemic areas, should be aware of the ophthalmological manifestations and complications of sporotrichosis.